Realization of Distributive Justice with the Approach of Intelligence or Artificial Intelligence - Kazem Elioon; Kheirollah Parvin; Mostafa Seraji (حقوق فناوریهای نوین)
Artificial intelligence is one of the most basic and serious topics of research and investigation in the world today. Artificial intelligence is progressing and developing in a lightning-fast and amazing manner in the current era. Very soon, we will see huge changes and developments in this type of new technology. This new technique and technology has been widely used internationally in various professions and industries. The profession of law, law, and distributive justice is not exempt from this issue; now this question is raised, which of the tools will be more useful and appropriate to achieve distributive justice; Human intelligence or artificial intelligence? Is it possible to bring society closer to real justice and fairness with this new technology in this modern era? What is certain is that artificial intelligence with the behavior of human intelligence strengthens capabilities and increases efficiency. Therefore, the findings using descriptive, analytical, and argumentative methods show that artificial intelligence in terms of speed, accuracy, and decision-making power in analysis and problem analysis is more effective and efficient compared to human intelligence. Thus, the use of this new technology helps a lot in the fair distribution of incomes, opportunities, and important economic issues in society. Although the negative effects caused by the expansion of this new technology cause economic, educational, moral, and other discriminations and inequalities; however, it is possible to reduce the negative effects of these inequalities caused by the development of this new technology by exercising caution, carefully managing and monitoring data, creating programs and supporting laws, and using artificial intelligence technology based on the principles of distributive justice.